2020
DOI: 10.2147/ott.s269606
|View full text |Cite
|
Sign up to set email alerts
|

<p>RNF128 Promotes Malignant Behaviors via EGFR/MEK/ERK Pathway in Hepatocellular Carcinoma</p>

Abstract: Background: The ubiquitin-proteasome system participates in the pathogenesis and progression of hepatocellular carcinoma (HCC). As an E3 ubiquitin ligase, RNF128 has been proved vital in carcinogenesis, whereas, little is known about the oncogenic mechanisms of RNF128 in HCC. Materials and Methods: Through tissue microarray from HCC patients, we analyzed RNF128 expression and its relationship with clinical outcomes in HCC. Western blot and quantitative realtime polymerase chain reaction (qRT-PCR) were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Rnf128 and Serpinb9b proved to be critical for leukemia development in RL-MuLV-infected SPF mice (Figure 5A). In line with our results, overexpression of the members of the ovalbumin family of serpins, to which Serpinb9b belongs, as well as Rnf128, are markers for poor prognosis in some human cancers [(Bai et al, 2020; ten Berge et al, 2002; Uhlen et al, 2017) and our own analysis of previously published data (Bolouri et al, 2018)]. A homolog for Serpinb9b has not been identified in humans, but related family member, human proteinase inhibitor 9 (SerpinB9) inhibits perforin-mediated cytotoxic T lymphocyte (CTL) cytotoxicity (Medema et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Rnf128 and Serpinb9b proved to be critical for leukemia development in RL-MuLV-infected SPF mice (Figure 5A). In line with our results, overexpression of the members of the ovalbumin family of serpins, to which Serpinb9b belongs, as well as Rnf128, are markers for poor prognosis in some human cancers [(Bai et al, 2020; ten Berge et al, 2002; Uhlen et al, 2017) and our own analysis of previously published data (Bolouri et al, 2018)]. A homolog for Serpinb9b has not been identified in humans, but related family member, human proteinase inhibitor 9 (SerpinB9) inhibits perforin-mediated cytotoxic T lymphocyte (CTL) cytotoxicity (Medema et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Recently, RNF128 has been shown to be responsible for tumorigenesis and metastasis of human cancers. Emerging evidence has suggested that RNF128 is aberrantly expressed in melanoma, esophageal cancer, bladder cancer, and hepatocellular carcinoma (HCC; Bai et al, 2020; Gao et al, 2019; Lee et al, 2016; Wei et al, 2019). Bai et al (2020) reported that HCC patients had a higher expression of RNF128 in tumor specimens than in matched para‐cancerous samples, and its high expression had a significant correlation to tumor size, TNM classification, and adverse oncological outcomes of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has suggested that RNF128 is aberrantly expressed in melanoma, esophageal cancer, bladder cancer, and hepatocellular carcinoma (HCC; Bai et al, 2020; Gao et al, 2019; Lee et al, 2016; Wei et al, 2019). Bai et al (2020) reported that HCC patients had a higher expression of RNF128 in tumor specimens than in matched para‐cancerous samples, and its high expression had a significant correlation to tumor size, TNM classification, and adverse oncological outcomes of HCC patients. A series of experimental study on the biological functions of HCC cells revealed that RNF128 inhibited cell apoptosis and promoted HCC proliferation, migration, and invasion by activating the EGFR/MEK/ERK pathway (Bai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances in targeted therapies for HCC, therapeutic responses in patients with HCC patients remain poor. Thus, it is imperative to develop effective therapeutic strategies against HCC to improve patient survival [7,8].…”
Section: Introductionmentioning
confidence: 99%